2020
DOI: 10.1038/s41598-020-67321-x
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the Edinburgh Postnatal Depression Scale in the Japan Environment and Children’s Study

Abstract: The Edinburgh Postnatal Depression Scale (EPDS) is frequently used to screen for postpartum depression. However, its factor structure exhibits noticeable inconsistencies between studies. We examined the EPDS at two postpartum time points using a large dataset from outside Western countries. Participants were 91,063 mothers in an ongoing birth cohort of the Japan Environment and Children’s Study. One-, two-, and three-factor structures of the EPDS at 1- and 6-months postpartum were extracted using exploratory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 62 publications
4
21
1
2
Order By: Relevance
“…Postpartum depression at 1 month after delivery was assessed using the Edinburgh Postnatal Depression Scale (EPDS), with a score of ≥ 9 used as a cut-off [35,36] to categorize results. Cronbach's alpha for the EPDS was 0.82, as shown in our previous study [37].…”
Section: Covariatessupporting
confidence: 81%
“…Postpartum depression at 1 month after delivery was assessed using the Edinburgh Postnatal Depression Scale (EPDS), with a score of ≥ 9 used as a cut-off [35,36] to categorize results. Cronbach's alpha for the EPDS was 0.82, as shown in our previous study [37].…”
Section: Covariatessupporting
confidence: 81%
“…A recent Japanese study using a large dataset revealed a three-factor structure model consisting of “Anhedonia” (Items 1 and 2), “Anxiety” (Items 3, 4, 5, and 6), and “Depression” (Items 7, 9, and 10). This model demonstrated a high goodness-of-fit [ 36 ]. On the other hand, a Japanese study using a cluster analysis suggested the presence of mothers with pathological maternal bonding (14.4%), with an optimal MIBS cut-off score of 4/5 at 1 month after delivery [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mothers with postpartum depression symptoms had child-rearing anxiety and exhaustion even when their children were five years old, and their children often behaved in a worrisome manner [ 36 ]. The EPDS also includes items that indicate depression, and studies that analyzed factor structure identified factors related to anxiety and depression [ 37 , 38 ]. As the EPDS predicted child-rearing anxiety at the 3-year-old checkup, it may lead to difficulties raising children.…”
Section: Discussionmentioning
confidence: 99%